European Food Systems in a Regional Perspective: A Comparative Study of the Effect of COVID-19 on Households and City-Region Food Systems - Millard, Jeremy; Sturla, Alberto; Smutná, Zdeňka; Duží, Barbora; Janssen, Meike; Vávra, Jan (Frontiers in Sustainable Food Systems, 2022)
The concept of the city-region food system is gaining attention due to the need to improve food availability, quality and environmental benefits, for example through sustainable agri-food strategies. The COVID-19 pandemic has reinforced the importance of coherent and inclusive food governance, especially regarding food resilience, vulnerability and justice. Given that evidence from good practices is relatively sparse, it is important to better understand the role of different types of cities, regions and household characteristics. The paper's aim is to describe, analyze and attempt to explain (sub-national) regional variations of household food behavior before and during the first wave of COVID-19 in 2020 using a city-region food system perspective. Informed by the literature, comprehensive survey data from 12 countries across Europe is used to describe the pre-pandemic landscape of different household food behaviors across comparable regional types. We examine how a specific economic and social shock can disrupt this behavior and the implications for city-region food systems and policies. Conclusions include the huge disruptions imposed on income-weak households and that the small city scale is the most resilient. Proposals are made that can strengthen European city-region food system resilience and sustainability, especially given that future shocks are highly likely.